HUBUNGAN MODAL MANUSIA DAN PERTUMBUHAN EKONOMI (SYSTEMATIC LITERATURE REVIEW) - Vandy Akhmad, - (2022)
This research is based on the problem of the contribution of human capital, where in a country there are factors that influence economic growth, one of which is human capital. The purpose of this study was to determine the relationship between human capital and economic growth in a country. The research method used is a systematic literature review. The search for relevant articles was carried out on online publications from the Scopus database published from 2001 to 2020. The authors obtained 10 articles that met the criteria based on the selection of the relevant articles that had been determined. The findings of the article show that human capital has a positive relationship to economic growth. This is because human capital can encourage economic improvement in a country with facilities to improve the quality of human capital, among others through education, health, on-the-job training, knowledge and work experience. So that in the end human capital is able to contribute to the economic growth of a country